(untitled) (Journal of Medicine, 2019)
Background: Serum tumor markers are convenient, non-invasive, acceptable to patients and play an important role as an ancillary tumor diagnostic tool. CA 19-9 has become a common tumor marker, specific for digestive system tumors. The study was carried out to determine the value of CA 19-9 as a tumor screening marker among healthy individuals. Materials and Methods: This study had been carried in Dhaka Medical college Hospital from January 2016 to January 2018. The serum CA 19-9 level was detected using a microsome luminescence method. Individuals with high CA 19-9 levels underwent further examination, including routine fecal testing, thoracic and abdominal computed tomography (CT) scan, gastroscopy, and colonoscopy. These individuals had regular follow-up examinations. Results: Over a 3-year period, the serum CA19-9 levels of 960 healthy individuals were estimated. The CA 19-9 level of 15 individuals was positive (positive rate: 1.56%), including 7 men (7/699; 1.001%) and 8 women (8/261; 3.06%). There was a significant difference between males and females (p<0.01), The overall tumor detection rate was 0.72% (7/960) including 6/699 men (0.85%) and 1/261 women (0.38%). Conclusion: Therefore, elevated CA 19-9 level can be used to assist in the diagnosis malignancy. J MEDICINE JUL 2019; 20 (2) : 92-94